2020
DOI: 10.21273/hortsci14409-19
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Variability of Irrigated Garlic (Allium sativum L.) Production Components

Abstract: Among the crops that are usually grown under irrigation, one can mention garlic, which is a product with high demand in Brazil and the world, it is highly valued in the cuisine of several countries, and is an aggregated crop with high economic value. In 2018, this work was conducted in Yellow Red Latosol. The objective was to characterize the structure and magnitude of the spatial distribution of garlic production components and to map the productive components to visualize spatial distribution and to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 8 publications
2
6
0
2
Order By: Relevance
“…Crosssemivariograms adjusted to the spherical and Gaussian models. Oliveira et al (2020a) also found the same adjustment models in a study performed with soil physical attributes.…”
Section: Resultssupporting
confidence: 64%
See 2 more Smart Citations
“…Crosssemivariograms adjusted to the spherical and Gaussian models. Oliveira et al (2020a) also found the same adjustment models in a study performed with soil physical attributes.…”
Section: Resultssupporting
confidence: 64%
“…Table 1 shows the descriptive analysis of the studied attributes. Oliveira et al (2020a) observed that the variability of an attribute can be classified according to the magnitude of its coefficient of variation (CV). The classes were determined as low (CV < 10%), medium (10% < CV < 20%), high (20% < CV < 30%), and very high (CV > 30%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the increase in the use of precision agriculture in Brazil, geostatistical studies on agronomic attributes related to productivity have been intensified. Precision agriculture is composed of a set of techniques that help farmers manage their crops, increasing production and income, as well as fertilization, harvesting, and spraying efficiencies, thus improving the final quality of the product (Oliveira et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…descreve as funções que este nutriente exerce nas plantas, tais como componentes dos fosfolipídios, ATP, DNA, RNA, açúcares fosfatos e outras moléculas fundamentais no crescimento dos vegetais e neste caso o desenvolvimento dos grãos.O coeficiente de determinação neste estudo foi de 0.9226 que pelo seu alto coeficiente pode ser agregado em próximas melhorias e desenvolvimento para a cultura do milho grão. Cultura muito importante em todo o mundo Oliveira et al, (2020),. e…”
unclassified